Acutely Reconstructed Isolated Supraclavicular Brachial Plexus Injury Caused By a Chainsaw. (March 2016) - Kaiser, Radek; Ullas, Gautham
Lacerations to the brachial plexus are rare. The author describes a case involving a man who sustained a chainsaw wound to the neck with isolated injury to the proximal part of the upper trunk of the brachial plexus. The patient underwent acute surgical exploration. After resection of the lacerated ends of the nerve stumps, four nerve grafts from the sural nerve were used for the reconstruction. Reinnervation was successful and the patient was able to abduct his arm (Medical Research Council 5 of 5) and flex his elbow (Medical Research Council 4 of 5) to its full range, within 24 months.